2013
DOI: 10.3171/2013.7.spine12352
|View full text |Cite
|
Sign up to set email alerts
|

Complex regional pain syndrome following lateral lumbar interbody fusion

Abstract: The minimally destructive lateral transpsoas approach to the spine has been used in the treatment of various lumbar spinal pathologies. Approach-specific complications have been reported due to the unique surgical corridor and lateral anatomical structures. The authors report a case of complex regional pain syndrome (CRPS) following interbody cage placement utilizing the lateral lumbar transpsoas approach. A review of the literature is discussed. Further clarification of the mechanism of CRPS and its t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…However, some author reported complications LLIF. Symptoms included pain, numbness, paresthesias, or weakness due to direct muscle injury and injury to the lumbar plexus as it courses through the psoas [19, 20]. Furthermore, high rates (62.7%) of transient anterior thigh symptoms are found despite real-time electromyography (EMG) monitoring [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, some author reported complications LLIF. Symptoms included pain, numbness, paresthesias, or weakness due to direct muscle injury and injury to the lumbar plexus as it courses through the psoas [19, 20]. Furthermore, high rates (62.7%) of transient anterior thigh symptoms are found despite real-time electromyography (EMG) monitoring [21].…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms usually resolve in mean time between 2 and 40 days. It is revealed from the review that in degenerative lumbar pathology [16,31,38,39], the relationship with the onset and causes of CRPS is more complex. In fact, many authors initially stated that the pain syndrome could be related to nerve, ganglion, or nerve root compression or impingement [38,39], but this was followed in the majority of cases (71/72) by spontaneous or only pharmacological resolution, without recourse to a second surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It is revealed from the review that in degenerative lumbar pathology [16,31,38,39], the relationship with the onset and causes of CRPS is more complex. In fact, many authors initially stated that the pain syndrome could be related to nerve, ganglion, or nerve root compression or impingement [38,39], but this was followed in the majority of cases (71/72) by spontaneous or only pharmacological resolution, without recourse to a second surgery. CRPS is always a diagnosis of exclusion, after proper evaluation of a well-positioned surgical procedure and implant, but it should be considered among the hypotheses from the outset in order to avoid the risk of an unnecessary second surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported the complications of lateral lumbar interbody fusion (LLIF) through transpsoas approach, such as anterior thigh pain, numbness, paresthesias or weakness due to direct muscle injury and injury to the lumbaplexus as it courses through the psoas [30]. OLIF through the approach between great vessel Zhou and Gu Journal of Orthopaedic Surgery and Research (2023) 18:117 and psoas was introduced as an alternative procedure to the transpsoas approach, allowing for psoas preservation and avoids the lumbar plexus [7,8].…”
Section: Pre-op Post-op 1 Month 2 Months 3 Months 6 Months 1 Year 2 Y...mentioning
confidence: 99%